Инквизитор: роман / Александр Мазин - Мазин Александр Владимирович (Азбука-триллер, 1996)
Экземпляры: аб. (2003) / Инвентарный номер: 46882 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44